A biogeographical assessment of deep-sea coral assemblages from coastwide visual surveys off California. (July 2022) - Watters, Diana L.; Laidig, Thomas E.; Yoklavich, Mary M.
Abstract: During the period 1992–2014, we quantified 79, 233 deep-sea corals (DSC; azooxanthellate corals occurring in cold or deep waters, generally >50 m) at depths 23–867 m from 1281 visual transects in areas of rocky substrata off northern, central, and southern California. DSC were present on 68% of transects at all depths and substrata types. Thirty-nine taxa and morphotypes from at least 19 families and 24 genera, including 20 species, were identified. Survey depths differed among study regions, overlapping between north and south at >575 m, and between central and south at <325 m. Within study regions, we examined taxa-specific depth and temperature ranges and quantified the spatial distribution of DSC densities. Across study regions, we interpreted species distributions in the context of the literature and biogeographic provinces off California, examined size distributions, and characterized assemblages relative to latitude and depth. We discovered depth range extensions for seven species, and provide the first taxa-specific in situ temperature data for the U.S. West Coast. Overall densities (number of colonies/100 m 2 ) of DSC within study regions were 105.8 (north), 5.0 (central), and 7.3 (south), and highest densities occurred on mixed and hard substrata. We did not observe a change in density with depth. Density 'hot' spots (p < 0.05) were identified at multiple locations in the central and south regions for DSC (other than sea pens) and for sea pens, respectively. Despite survey depth differences, three species with large depth ranges were observed in all three study regions, and most species were observed in the biogeographical province(s) reported for them in the literature. Most DSC were ≤20 cm high and ≤10 cm wide; colonies >50 cm high and >40 cm wide were rare and found primarily in the south. Six DSC assemblages (p < 0.05) were identified. Mid-depth assemblages in the central and south differed considerably, while deep assemblages in the north and south were similar. A shallow assemblage comprised taxa shared by central and south regions. As the relative habitat value of DSC to fishes becomes more apparent, our results will provide invaluable information for the identification of essential fish habitat and priority areas in need of protection.